Epidemiologic analysis of antimicrobial resistance in hospital departments in China from 2022 to 2023 - Hui-Jun Bai; Qing-Feng Geng; Fang Jin; Yong-Li Yang (BMC, 2024)
Abstract Bacterial drug resistance monitoring in hospitals is a crucial aspect of healthcare management and a growing concern worldwide. In this study, we analysed the bacterial drug resistance surveillance in our hospital from 2022 Q1 to 2023 Q2. The main sampling sources were respiratory, blood, and urine-based, and the main clinical infections were respiratory and genitourinary in nature. Specimens were inoculated and cultured; bacterial strains were isolated using a VITEK® 2 Compact 60-card automatic microorganism identifier (bioMerieux, Paris, France) and their matching identification cards were identified, and manual tests were supplemented for strain identification. The most common Gram-positive bacteria detected were Staphylococcus aureus, followed by Enterococcus faecalis (E. faecalis), Staphylococcus epidermidis (S. epidermidis), and Staphylococcus haemolyticus (S. haemolyticus). The most common Gram-negative bacteria detected were Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. The most prevalent multidrug-resistant bacteria were those producing extended-spectrum beta-lactamases, followed by methicillin-resistant Staphylococcus aureus, followed by carbapenem-resistant Enterobacterales. This study suggests that the prevention and control of infections in the respiratory and genitourinary systems should be the focus of anti-infective work and that the use of antimicrobials should be reduced and regulated to prevent the emergence and spread of resistant bacteria.